ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI EKSPOR TEKSTIL DI INDONESIA TAHUN 2005 – 2009 - Mey Richa Madya Lestari (Jurnal Ekonomi Pembangunan, 2011)
The type of the research was descriptive quantitative, entitled "Analysis of Factors - Factors Affecting the Export of Textile in Indonesia in 2005.1–2009.4". In this study, the researcher took the hypothesis that there were effect between PDB, Exchange Rate and Inflation on Textile Exports in Indonesia in 2005.1 - 2009.4. The analysis tools used a statistical test approach was called the test of significance, the decision to accept and reject Ho made on the basis of statistical values (t test and F test). From the data analysis which has been conducted simultaneously indicates that the variable exchange rates had a more significant outcome of the Textiles Export. This could be seen from the significance, namely PDB variable (2.430), Exchange Rates (-3.039), and Inflation (1.944). Besides, it could also be seen from the F test, which Fcount > F table that was about 4.402 > 2.28.